Multimodal imaging of thyroid cancer. Issue 5 (October 2020) - Brauckhoff, Katrin; Biermann, Martin
Abstract : Purpose of review: Thyroid cancer is the most common endocrine cancer in adults with rising incidence. Challenges in imaging thyroid cancer are twofold: distinguishing thyroid cancer from benign thyroid nodules, which occur in 50% of the population over 50 years; and correct staging of thyroid cancer to facilitate appropriate radical surgery in a single session. The clinical management of thyroid cancer patients has been covered in detail by the 2015 guidelines of the American Thyroid Association (ATA). The purpose of this review is to state the principles underlying optimal multimodal imaging of thyroid cancer and aid clinicians in avoiding important pitfalls. Recent findings: Recent additions to the literature include assessment of ultrasound-based scoring systems to improve selection of nodules for fine needle biopsy (FNB) and the evaluation of new radioactive tracers for imaging thyroid cancer. Summary: The mainstay of diagnosing thyroid cancer is thyroid ultrasound with ultrasound-guided FNB. Contrast-enhanced computed tomography and PET with [ 18 F]-fluorodeoxyglucose (FDG) and MRI are reserved for advanced and/or recurrent cases of differentiated thyroid cancer and anaplastic thyroid cancer, while [ 18 F]FDOPA and [ 68 Ga]DOTATOC are the preferred tracers for medullary thyroid cancer.